Análise filogenética de espécies selecionadas do gênero Eunice (Eunicidae, Polychaeta) - Zanol, Joana (2002)
Most specimens examined in previous studies of the genus Eunice have been incomplete. This lead problems in the taxonomy of the genus, large amount of missing characters in cladistic analyses and inconclusive results. ln this study, complete specimens of 23 species of Eunice were examined and a cladistic analysis was performed. The purpose was to define monophyletic groups within Eunice that could be used to divide this genus into "new" genera, since it has been shown to be paraphyletic in a previous analysis. Some of the coded characters were used for the first time, most of them features of the buccal apparatus. Eunice sensu lato was divided in three clades, and the genera Marphysa, Lysidice and Palola fell inside it. A common feature to the present, preliminary and former results was the placement of Eunice antennata and Eunice aphroditois in clades apart. Perhaps one corresponds to the old genus Leodice, since it includes E. antennata, its type species. The clade including E. aphroditois, type species of the genus Eunice, may be considered as Eunice sensu stricto. The third group, which may be the result of a misrepresentation of the diversity of species, will most probably turn out to be invalid in future analyses. The groups usually used to subdivide the genus Eunice, based on the color and dentition of the subacicular hooks and branchial distribution, were shown to be paraphyletic.